Aerogel sheet of carbon nanotubes decorated with palladium nanoparticles for hydrogen gas sensing. (22nd March 2018) - Kim, Ju Hyeon; Jeon, Jei Gyeong; Ovalle-Robles, Raquel; Kang, Tae June
Abstract: In the development of hydrogen sensors, it is required to meet the demands of both high sensor performance as well as the ease of fabrication for mass production. For this purpose we proposed a chemiresistive hydrogen sensors based on an aerogel sheet of carbon nanotubes decorated with palladium nanoparticles (CNT/Pd sheet). The fabrication process is straightforward that a dry-spun CNT aerogel sheet is suspended between concentric electrodes followed by depositing Pd nanoparticles on CNT sheets by thermal evaporation. The present CNT/Pd sheet sensors can detect hydrogen at concentrations as low as 2 ppm at room temperature with a detection range from 2 to 1000 ppm. The aerogel nature of CNT/Pd sheet contributes to low detection limit and broad detection range of the CNT/Pd sensor. Relations between hydrogen concentration and sensor response and response time, and the effects of temperature on sensor performance were investigated. Graphical abstract: Highlights: High performance CNT/Pd sheet hydrogen sensor arrays is fabricated. The LOD is 2 ppm at room temperature with a detection range from 2 to 1000 ppm. Relations between hydrogen concentration and sensor response and response time were investigated. The aerogel nature of CNT/Pd sheet contributes to low detection limit and broad detection range.